2007
DOI: 10.1021/jo0700934
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Aminolysis of Aryl Phenyl Chlorothiophosphates with Anilines

Abstract: Kinetic studies of the reactions of aryl phenyl chlorothiophosphates (1) and aryl 4-chlorophenyl chlorothiophosphates (2) with substituted anilines in acetonitrile at 55.0 degrees C are reported. The negative values of the cross-interaction constant rhoXY (rhoXY = -0.22 and -0.50 for 1 and 2, respectively) between substituents in the nucleophile (X) and substrate (Y) indicate that the reactions proceed by concerted SN2 mechanism. The primary kinetic isotope effects (kH/kD = 1.11-1.13 and 1.10-1.46 for 1 and 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(18 citation statements)
references
References 70 publications
0
17
1
Order By: Relevance
“…(3), pure second-, third-, and higher-derivative terms are not considered as in Eq. (1). The values of ρ X(H) , ρ Y(H) , ρ XY(H) and ρ YY(H) obtained by multiple regression are described in Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…(3), pure second-, third-, and higher-derivative terms are not considered as in Eq. (1). The values of ρ X(H) , ρ Y(H) , ρ XY(H) and ρ YY(H) obtained by multiple regression are described in Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…The anilinolyses of tetracoordinate phosphorus with the Cl -leaving group have been studied extensively in this laboratory, and the data obtained for primary normal DKIEs involving deuterated anilines were rationalized by TSf-type, in which hydrogen bonding of an amine hydrogen atom occurs to the departing chloride. [32][33][34][35][36][37][38] The authors also suggested TSf-type in which hydrogen bonding of an amine hydrogen atom occurs to the departing phenoxy oxygen atom for the anilinolyses of aryl dimethyl, methyl and diphenyl phosphinates. Table 5 lists the activation parameters, enthalpies and entropies of activation, for the reactions of Y-aryl ethyl isothiocyanophosphates with unsubstituted aniline.…”
Section: -7mentioning
confidence: 99%
“…2,5,[6][7][8] The anilinolyses 5,6,7a-j and pyridinolyses 2,8a,c,e,f,g of R 1 R 2 P(=O or S)Cl-type substrates are extensively studied in MeCN. A backside and frontside nucleophilic attack were discussed on the basis of the deuterium kinetic isotope effects (DKIEs; k H /k D ), selectivity parameters (ρ X , ρ Y , β X , and ρ XY ) and free energy correlations (linear, biphasic concave upwards/downwards) for variation of substituent X and Y in the nucleophile and substrate, respectively.…”
Section: 7dmentioning
confidence: 99%
“…2,[5][6][7]15 The real primary normal DKIE due to the hydrogen bond between the hydrogen of the N-H(D) moiety and the leaving group should be greater than the observed value, since the secondary inverse DKIE (k H /k D < 1) because of the steric hindrance that increases the out-of-plane bending vibrational The reaction mechanism of the anilinolyses of R 1 R 2 P (=O or S)Cl in MeCN in Table 1 were rationalized mainly based on the cross-interaction constants (CICs), 16 selectivity parameters (ρ X and β X ), and DKIEs. In O(PhO,PhO) and S(PhO,PhO), a concerted S N 2 mechanism was proposed on the basis of a negative ρ XY value (ρ XY = -1.31 and -0.22, respectively).…”
Section: 7dmentioning
confidence: 99%